IMPLEMENTATION OF LAW NUMBER 11 OF 2008 ON ELECTRONIC INFORMATION AND TRANSACTIONS AGAINST THE RISE OF HOAX CULTURE DURING COVID-19 PANDEMIC IN INDONESIA - Asri Agustiwi; Raka Widya Nugraha; Dania Rama Pratiwi (Universitas Surakarta, 2020)
This article aims to find out the implementation of Law No. 11 of 2008 on Electronic Information and Transactions against the spread of hoaxes during the COVID-19 pandemic in Indonesia as well as how to prevent the growing culture of hoax information spreading in Indonesia. The research method used is a normative method with the study of the Law, while the secondary data material used is the study library as well as the approach of laws and concepts. The result obtained is Law No. 11/2008 jo No. 19/2016 Article 28 paragraphs 1 and 2 has been effective because it can limit the wiggle room of the perpetrators of news and hate speech. More specifically, the perpetrator can be ensaned with other relevant Articles namely Article 311 and 378 of the Consumer Order, Article 27 paragraph 3 of Law No. 19 of 2016 on Electronic Information and Transactions. The role of society, journalists and parents is indispensable also in preventing the dissemination of such fake news. Many steps can be taken, especially as the reader should not immediately believe there needs to be a study by comparing an information with other information. Keywords: hoax, Covid-19, Electronic Information And Transaction Act.